The commercialisation of tucumã (Astrocaryum aculeatum) by extractivists in riverside communities in the Amazon - Silva, Lindomar de Jesus de Sousa; Schneider, Sergio; Santos, Alessandro Carvalho dos; Meneghetti, Gilmar Antonio; Pinheiro, José Olenilson Costa; Alves, Rosilane Bruna de Souza (Sustainability in Debate, 2024)
The article presents the results of research on the commercialisation channels of tucumã, a product of extractivism which expresses an aspect of the food culture of the Amazonians. The research was carried out in three communities (São Francisco do Mainã, Jatuarana and Novo Progresso) located on the left bank of the Amazon and with farmers from the Puraquequara region, Manaus - AM. The research had a quantitative and qualitative bias. In all, 30 farmers who extract tucumã were interviewed. The research showed the tucumã commercialisation dynamics, quantifying and shedding light on the commercialisation channels and the relationships established in the commercialisation and shows the weaknesses of the actors involved, especially the extractive farmers. The information can help in the elaboration of actions to support the actors involved in the activity.